The effects of systematic risks on bank asset quality : evidence from organisation of the petroleum exporting countries (OPEC) - Idris, Isma'il Tijjani (2017)
The global position of Non-Performing Loans (NPLs) is persistent and on the rise which indicates a global deterioration of bank asset quality. The problem is more pronounced among the Organisation of the Petroleum Exporting Countries (OPEC) whose ratio of NPLs is on the verge of the banking crisis. The objective of this study is to investigate the effects of the prevalence of systematic risk factors in the OPEC countries on the deterioration of their bank asset quality. In achieving this objective, the study employed the panel data set of the entire OPEC countries spanning 1996-2015. Further, to account for NPL persistence, the study employed Pooled Mean Group (PMG) model in its estimations. The findings reveal that an increase in oil price improves bank asset quality which signifies that a rise in oil price inversely affects NPLs. On the other hand, a rise in the level of corruption increases the level of NPLs which indicates that corruption positively affects NPLs. Further, an increase in the level of political instability deteriorates the level of bank asset quality which means that an increase in the level of political instability positively affects NPLs. Additionally, the result reveals that an increase in environmental risks raises the level of NPLs which denotes that an increase in the occurrence of environmental risk positively affects NPLs. Overall, the findings imply that the prevalence of systematic risks in OPEC countries adversely affect bank asset quality and are key to financial stability. Consequently, the results imply that policymakers should design appropriate prudential policies that will curtail the impact of these systematic risks on bank asset quality and diversification of their economies which will ensure sustainable financial stability amongst OPEC countries.